Does Islamic Financial Inclusion Matter for Household Financial Well Being? - Hamida, Ambas; Muhajir, Muhammad Nur Alam; Sukran, Sukran; Paulus, Muni (Jurnal Keuangan dan Perbankan, 2023)
This study aims to analyze the effect of islamic financial inclusion on financial well being by measuring the relationship between each dimension or the construction of research variables. The data was collected from 100 households using the services of Islamic financial institutions in Indonesia. Analysis of the structural equation model–partial least square (SEM-PLS) was conducted to analyze the relationship between variables and test a series of hypotheses. The results showed that access had a significant effect on financial satisfaction, financial safety and household financial worries. Dimensions and construction usage have a positive effect on financial satisfied, financial safety and household emergency funds. Meanwhile, construction quality has an effect on household financial safety. This study will determine the policy makers of the Islamic financial sector in planning services and improving access, quality and usage of Islamic financial services. This research will also increase household knowledge about household financial management.JEL: D1, G5, I3